Foreshadowing: Narrative Gravity in the Autumnal Chronotope of Short Stories by Aumonier and Jacobs - Rai, Bimalendra (Journal of Innovation in Academia, 2025)
This study re-examines how setting operates as an active narrative force by analyzing Stacy Aumonier’s “The Perfect Murder” and W. W. Jacobs’s “The Interruption.” While existing narratological frameworks have theorized Bakhtin’s chronotope and anticipation as separate components, they have not sufficiently explained how environmental conditions produce anticipatory pressure within the storyworld. Using qualitative close reading and an interdisciplinary synthesis of Bakhtin’s chronotope, phenomenological accounts of mood and atmosphere, and temporal theories from Genette and Brooks, the study argues that the lateautumn environments in both stories function as fused narrative chronotopic fields rather than descriptive backdrops. The analysis identifies a shared “harvest-before-death” chronotope in which November atmospheres externalize psychological instability and render outcomes feel inevitable by constraining character agency. Building on these findings, the article advances narrative gravity as a theoretical model that pulls the storyworld towards its endings long before events unfold.